2011 International meeting of the Korean society for aesthetic plastic surgery & the Korean Association of plastic surgeons - Lye, Khoo Teng (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
increasingly popular among the public for scar prevention and treatment.